On the Road to Graphicacy: The learning of graphical representation systems - Postigo, Yolanda; Pozo, Juan Ignacio (Educational psychology (Dorchester-on-Thames), 2004)
This article examines the learning of different types of graphic information by subjects with different levels of education and knowledge of the content represented. Three levels of graphic information learning were distinguished (explicit, implicit, and conceptual information processing) and two experiments were conducted, looking at graph and geographical map learning. The graph study (Experiment 1) examined the influence of the variables' numerical relationship structure on adolescent students with different levels of education and knowledge of social sciences and also assessed their proportional reasoning skills. The map study (Experiment 2) looked at the learning of a geographical map studied spontaneously by secondary school and university students with different geographical knowledge (experts and novices) and also assessed their spatial skills. The results of both studies show that graph and map learning performance improves with the subjects' educational level. The groups' differential performance varied according to the type of information involved (explicit, implicit, or conceptual). The subjects' knowledge of the domain in question determined the level at which they processed the information. Verbal and superficial processing of graphic information were also found to predominate. This has important educational implications, suggesting the need for differential treatment in teaching different types of information. The results of the study also raise interesting issues regarding the type of expertise involved in learning graphic information: expertise related to the content represented, to knowledge of the syntax (graphicacy), and/or the system of knowledge graphically represented - spatial in the case of maps, numerical in the case of graphs.